Correlation of functional capacity between six minute walk test and six minute step test in chronic obstructive pulmonary disease patients. - D.ANANDHI; DARSHNI.R.THAKKAR; PROF.V.P.R.SIVAKUMAR (International Journal of Pharma and Bio Sciences, 2017)
To find the Correlation of Functional Capacity between Six Minute Walk Test and Six Minute Step Test. Non experimental study design. 20 patients with Chronic Obstructive Pulmonary Disease with age group 30-85 years of both genders, being mild (FEV1≥ 80%) to moderate (FEV150-79%). 20 patients performed Six Minute Walk Test on first day and Six Minute Step Test on second day.: Double Product, Borg Scale, Heart Rate and VO2 max. Statistical analysis was done by using Independent‘t’ test and Correlation test which showed there is significant difference between Heart rate (p<0.05), Double Product (p<0.05) and Borg Scale (p<0.05) in both the tests and there is no correlation of VO2 max (p>0.05) between both the test.: It is concluded that there is no correlation of functional capacity between Six Minute Walk Test and Six Minute Step Test in COPD patients.